Cultural indicators of well-being: Some conceptual issues - Prasanta K. Pattanaik (United Nations Research Institute for Social Development (UNRISD), 1997)
The joint UNRISD-UNESCO series of Occasional Papers on Culture and Development is a first step in facilitating and catalyzing an international debate on culture and development based on high-quality research. In this, the second paper in the series, the author considers some conceptual issues involved in constructing social indicators. To do so, he argues that well-being can be understood in terms of what Amartya Sen has called "functionnings", the "doings" and "beings" that people value.
Keywords: 330